Geology and SHRIMP U-Pb Geochronology of the Igarap Bahia Deposit, Carajs Copper-Gold Belt, Brazil: An Archean (2.57 Ga) Example of Iron-Oxide Cu-Au-(U-REE) Mineralization - Tallarico, F.; Figueiredo, B.; Groves, D.; Kositcin, N.; McNaughton, Neal; Fletcher, Ian; Rego, J. (Society of Economic Geologists Inc, 2005)
A striking feature of the Carajs region, Brazil, is the clustering of a variety of different types of Cu-Au deposits.The most abundant in the belt are the >200 million metric tons (Mt) of Fe oxide Cu-Au-(U-REE) deposits, which, despite the variety of host rocks and different orebody morphologies, share a number of diagnostic features, including (1) intense Fe metasomatism leading to the formation of grunerite, fayalite, and/or Fe oxides (magnetite and/or hematite); (2) intense carbonate alteration (mainly siderite); (3) sulfur-poor oremineralogy (chalcopyrite and bornite); (4) quartz-deficient gangue; (5) extreme low REE enrichment, and (6) enrichment in U and Co. The Igarap Bahia deposit is perhaps the best documented Fe oxide Cu-Au-(U-REE) deposit of the belt, containing about 219 Mt at 1.4 percent Cu and 0.86 g/t Au. The Cu-Au ore consists ofsteeply dipping breccia bodies that are hosted by hydrothermally altered metavolcano-sedimentary rocks. SHRIMP II zircon dating of the host metavolcanic rocks gives a 207Pb/206Pb age of 2748 34 Ma. This suggests a correlation between the Igarap Bahia volcano-sedimentary sequence and the Gro Par volcanic rocks, which have published ages of ca. 2.75 Ga. SHRIMP dating of monazite from the matrix of ore-bearing magnetite breccias gives a 207Pb/206Pb age of 2575 12 Ma, confirming the epigenetic nature of the mineralization and placing it ~175 m.y. after accumulation of the host volcano-sedimentary sequence. The 2575 12 Ma SHRIMP age of hydrothermal monazite from the Igarap Bahia mineralization is indistinguishable from published conventional 207Pb/206Pb ages for zircons from the Archean A-type granites of the Carajs belt, indicating that mineralization processes at Igarap Bahia were temporally related to these A-type Archean granites. The wide range of highly radiogenic 87Sr/86Sr ratios (0.714-0.755) of carbonates from the Igarap Bahia deposit suggests multiple crustal sources, consistent with a magmatic-hydrothermal origin. SHRIMP dating of zircon xenocrysts recovered from crosscutting diabase dikes indicates a maximum 207Pb/206Pb age of ~2670 Ma, consistent with field evidence and the age of host rocks, but does not unequivocably constrain the age of the ores.The styles of hydrothermal alteration, mineralogy, and geochemistry of the Igarap Bahia ore, as well as published fluid inclusion and stable isotope data, support its classification as a member of the world-class Olympic Dam-type Fe oxide Cu-Au-(U-REE) group of deposits, as previously argued by several authors. The SHRIMP age of 2575 12 Ma for hydrothermal monazite indicates that Igarap Bahia is an Archean example of this deposit group.